POLA KOMUNIKASI PROSTITUSI ONLINE : Studi Netnografi Pada Aplikasi MiChat - Zahra Maulidia Claresti, (2022)
This study aims to find out how the MiChat app is used as a medium for online prostitution practices, and also to find out the communication patterns in the online prostitution. This type of this study is descriptive qualitative using the netnographic method. The data data obtained from this study are primary and secondary. Data collection techniques in this study used observation techniques carried out online through the MiChat app, interviews, and documentation. Researcher use cyber media analysis in analyzing data that has four levels, namely the Media Space Level, Media Archive Level, Media Object Level, and Experiental Stories. After that, the data is verified using the triangulation method. The results of this study indicate that the MiChat app is used by sex workers by utilizing available features such as the People Nearby feature which is the main feature in the MiChat prostitution practice. There are three communication patterns that occur in the MiChat prostitution practice, namely secondary communication patterns, primary communication patterns, and circular communikation pattern.